Revisiting the mother-tongue medium controversy (2010)
A number of studies carried out on 'Primary School Dropouts' in Nigeria and elsewhere attributed the dropout phenomenon (which ranges from 40% to 60%) in certain countries to premature introduction of English as a language of instruction at the primary school. In the National Policy on Education (Revised in 1981), the mother-tongue medium policy was clearly and unambiguously stated for the first time. Since then, several experiments have been carried out to prove the efficacy of mother tongue as medium of instruction in the primary school. Notable among these is the Ife Six-Year Yoruba Primary-Project (SYYPP) 1970- 1975. This study provides answers to the following questions: (i) Are the proprietors of Private Nursery and Primary Schools aware of the mother-tongue medium policy? (ii) What is their attitude towards it? (iii) To what extent is the policy statement adhered to? (iv) If the policy is not-adhered to, what are the reasons given for not adhering to it? (v) What is the status of the so-called major languages and languages of the immediate community in these schools, that is, are they being taught as subjects? (vi) How many periods are allotted to them per week on the timetable, compared with exoglossic languages like English and French? (viii) What are the implications of all these on the so-called major languages of Nigeria and the languages of the immediate community? Answers to these questions form the basic thrust of this paper